Answer:
Step-by-step explanation:
y-x=0.7
y=x+0.7, so lets plug in that into the expressions instead of y
1)
(y-x)=
x+0.7-x=
x+0.7+(-x)=
x+(-x)+0.7=
x-x+0.7=
0.7
2)
(x-(x+0.7))/((x+0.7)-x)=
(x-x+0.7)/(x+0.7-x)=
(x-x+0.7)/(x+0.7+(-x))=
(x-x+0.7)/(x+(-x)+0.7)=
(x-x+0.7)/(x-x+0.7)=
0.7/0.7=
1
a
2/10 or 0.2
i dont know which tenths you wanted so i did both
7 miles
45 - 17 = 28 miles
28 : 4 = 7 miles
Answer: option B
-4, 1, 3
B
<em>Let's multiply this out and combine like terms:</em>
So there are 2 terms.
Answer choice B is right.